2009
DOI: 10.1080/13691050902721853
|View full text |Cite
|
Sign up to set email alerts
|

Intensive sex partying amongst gay men in Sydney

Abstract: Intensive sex partying is a framework developed to analyse specific frequent behaviours amongst a small minority of gay men in Sydney, Australia. The behaviours included a higher frequency of dance party attendance, more frequent sex, more anal sex, multiple sex partners, more unprotected anal intercourse with casual partners and more frequent drug taking. These occur at a contextual intersection between a sub-group of sexually adventurous gay men and 'party boys'. The men appear to be involved in both high-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 72 publications
3
55
0
Order By: Relevance
“…These include: being very sexually active; being closely involved in gay community social and sexual networks; engaging in group sex; engaging in CLAI; and using party drugs [15]. EDM use for intensive sex partying has been associated with sexual risk behaviors [3,4], such as increased numbers sex partners [2] and TABLE 1 About a quarter (26.2%) of men reported having more than ten male sex partners in the previous six months (Table 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include: being very sexually active; being closely involved in gay community social and sexual networks; engaging in group sex; engaging in CLAI; and using party drugs [15]. EDM use for intensive sex partying has been associated with sexual risk behaviors [3,4], such as increased numbers sex partners [2] and TABLE 1 About a quarter (26.2%) of men reported having more than ten male sex partners in the previous six months (Table 2).…”
Section: Introductionmentioning
confidence: 99%
“…Intensive sex partying has been described as a combination of several factors that are associated with the risk of HIV infection [15]. These include: being very sexually active; being closely involved in gay community social and sexual networks; engaging in group sex; engaging in CLAI; and using party drugs [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, it does raise interesting questions about whether the primary goal of polydrug use is an intensely pleasurable experience, in which considerations of sexual risk are secondary, or whether polydrug use is a device used both for intense pleasure and removal of inhibitions. 32 Another possibility is that a person-level mechanism drives this situational relationship between polydrug use, pleasure and sexual risk, although we were unable to examine this specific relationship.…”
Section: Discussionmentioning
confidence: 83%
“…As both illicit drug use and sex without condoms represent instances of sociomedical non-compliance, those who are led to breach one of these prescriptions may well be inclined to breach the other in certain circumstances, especially when such prescriptions fail to take into account the lived realities and constraints of people's everyday lives and desires. While men who engage in chemsex and 'party 'n' play' ('PnP') scenes do so for a range of reasons (including pleasure, adventure and enjoyment), 11,76 several studies have found associations between traumatic childhood incidents, such as childhood sexual abuse, the use of stimulants for sex and sexual risk-taking. 77,78 For some, sexualised drug use may operate as a form of affective experimentation that is undertaken with a view to reconfiguring prior, difficult bodily experiences.…”
Section: Sexualised Drug Usementioning
confidence: 99%